Comparison of the standardized incidence ratio of tuberculosis among workers at medical and educational institutions: a nationwide LTBI observational cohort study - Yun-Hee Lee; Ju Sang Kim; Young-Joon Park; Gahee Kim; Yujin Kim; Gyuri Park; Hyung Woo Kim; Jun-Pyo Myong (Elsevier, 2024)
Background: The objective of this study was to determine the incidence of tuberculosis (TB) among workers at medical institutions based on interferon-gamma release assay (IGRA) and compare it with that of workers at educational institutions and the general population. Methods: From March 2017 to December 2020, we used a cohort of workers from medical and educational institutions in Korea, who underwent IGRA as part of a national screening program for latent tuberculosis infection (LTBI). After connecting to the National Health Insurance Service (NHIS) database to detect for any actual cases of active TB, we estimated standardized incidence ratio (SIR) and the expected number of cases to compare the incidence of TB with that of the general population. Results: Significant disparities in TB incidence were revealed among workers in medical and educational institutions, based on IGRA results, age, and occupation. Individuals positive for IGRA in medical institutions displayed substantially higher SIR for TB, 7.19 (6.15-8.41), compared to counterparts in educational institutions, 3.69 (3.02-4.51). Comparing by age group, we see that the SIRs are higher in younger age groups compared to older ones, with 37.30 (28.11-49.50) and 11.89 (7.28-19.41) for IGRA-positive medical and education workers under 30 years of age, respectively. In the results by occupation within the medical institutions, nurses had the highest SIR at 14.17 (11.14-18.04). Conclusions: Healthcare workers in medical institutions are more likely to develop actual TB after a positive result of LTBI screening in Korea. Intensive management and surveillance programs should be reinforced.